2017
DOI: 10.12688/f1000research.12252.1
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum-to-Golgi transitions upon herpes virus infection

Abstract: Herpesvirus capsids are assembled in the nucleus before they Background are translocated to the perinuclear space by budding, acquiring tegument and envelope, or releasing to the cytoplasm in a "naked" state via impaired nuclear envelope. One model proposes that envelopment, "de-envelopment" and "re-envelopment" are essential steps for production of infectious virus. Glycoproteins gB/gH were reported to be essential for de-envelopment, by fusion of the "primary" envelope with the outer nuclear membrane. Yet, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…For instance, Herpes virus is formed within the nuclear envelope and then is transported toward the GC. Using high-resolution electron microscopy, COPII coated buds were not seen on the granular ER, with no COPII-coat in the ER domain where virions were localized (Wild et al, 2017). Also, separated vacuoles with a virion inside their lumen were not detected.…”
Section: Er-golgi Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Herpes virus is formed within the nuclear envelope and then is transported toward the GC. Using high-resolution electron microscopy, COPII coated buds were not seen on the granular ER, with no COPII-coat in the ER domain where virions were localized (Wild et al, 2017). Also, separated vacuoles with a virion inside their lumen were not detected.…”
Section: Er-golgi Transportmentioning
confidence: 99%
“…Also, separated vacuoles with a virion inside their lumen were not detected. They suggested that transport is realized according to a bolus-like mechanism along the ER tubule (see Figure 11 of Wild et al, 2017). It was shown that aggregates of PC are formed already inside the lumen of the ER cisternae (Figures 9–11 of Karim et al, 1979; see also Mironov et al, 2003).…”
Section: Er-golgi Transportmentioning
confidence: 99%
“…Here, we compared the CMPM and KARM and demonstrated that at steady-state and during synchronous IGT, all of the cargoes examined (including mega-cargos) became enriched at the trans -side of the Golgi complex. Many similar images that demonstrate this phenomenon have been published, but explanations were not presented [ 25 , 43 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ]. For instance, in previous papers, Clermont et al [ 66 ] and Rambourg et al [ 67 ] demonstrated that mega-cargoes are enriched at the trans -side of the Golgi complex.…”
Section: Discussionmentioning
confidence: 99%